The Effect of Service Quality and Consumer Trust on Interest in Using ShopeePay on the Shopee Application (Case Study of Regular C Students of Management Study Program at PASIM Bandung National University) - Desfitriady; Mallick Fazhar Insanny (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study’s aim was to ascertain how much influence service quality and consumer confidence have on interest in using ShopeePay in the Shopee application. The research methods used are descriptive methods and associative methods. The unit of analysis of this research is regular students and students of Management Study Program C at PASIM Bandung National University. Based on the results of sample calculations using saturated sampling techniques, seventy participants made up the study’s sample size. Multiple linear regression analysis are further analysis techniques the t-test and F-test are also carried out. Based on the research results, the independent variables (service quality and consumer confidence) show that there is factor that affects the dependent variable (interest in use) of 75.1%. The effect of service quality variables on usage interest is 17.6%, and the effect of consumer confidence on usage interest is 57.5%. The implication of this research is that companies should continue to improve quality and quality as well as features that are attractive and easy to use. As well as continuing to innovate and keep up with the era of digitalization so that the ShopeePay service feature can continue to grow and be of interest to many people